“The big topic is COVID”: A qualitative study about changes in HPV vaccine conversations between parents and primary care team members throughout the COVID-19 pandemic - Josheili Y. Llavona-Ortiz; Lauren J. Van Scoy; Benjamin Fogel; Casey Pinto; Jamelia Graham; William A. Calo (Human Vaccines & Immunotherapeutics)
Pandemic-related disruptions in primary care delayed important discussions between providers and parents about routine vaccinations. Conversations have become even more challenging since the COVID-19 pandemic due to increased vaccine hesitancy. This qualitative study explored changes in human papillomavirus (HPV) vaccine conversations within the context of the pandemic from the perspective of primary care team members (PCTMs). Twenty-five PCTMs serving children between 9 and 17 y old in Pennsylvania during the pandemic were conveniently sampled. PCTMs rated their confidence and agreement related to HPV vaccine conversations and pandemic impact. Semi-structured interview questions assessed changes in their HPV vaccine conversations throughout the pandemic. Open-ended questions inquired about PCTMs’ thoughts on the COVID-19 pandemic and if or how it impacted HPV vaccination uptake in their practice. Data were collected from May to July 2024. Verbatim transcriptions were analyzed using both inductive and deductive approaches to thematic analysis. Participants were 44% pediatricians, 50% had ≥20 y experience, and 68% were White. Six themes emerged: (1) parents show a range of reactions about HPV vaccination; (2) disruptions in healthcare visits and heightened parental concerns impede vaccination; (3) PCTMs notice clear changes in vaccine acceptance rates; (4) reasons for vaccination refusal have not substantially changed as a result of the pandemic; (5) importance of interpersonal relationships with parents; and (6) PCTM burnout impacts conversations. The pandemic added challenges to HPV vaccine conversations with parents. Findings from this study can be used to refine existing communication approaches to improve HPV vaccine conversations in primary care.